Novel polymer electrolyte based polyurethane acrylate for low-cost perovskite solar cells applications - M. Noor, I.; Rojudi, Z. E.; M. Ghazali, M. I.; Tamchek, N.; Nagao, Y. (Taylor and Francis, 2023)
Gel polymer electrolytes with polyurethane acrylate (PUA) and tetrapropylammonium iodide (TPAI) have been prepared. The maximum conductivity of (4.95 ± 0.02)×10−5 S cm−1 was obtained after 35 wt. TPAI is added to PUA (G5 electrolyte), dominated by the highest charge carrier mobility (µ). The perovskite solar cell (PSC) with G5 electrolyte displayed the highest power conversion efficiency of (0.206 ± 0.014), caused by the highest µ in electrolyte G5 that accelerates the electron transfer from the counter electrode to the ionized perovskite. This research proves that PUA can be exploited as a host polymer in polymer electrolytes for PSC applications.